Nickel-catalyzed enantioselective vinylation of aryl 2-azaallyl anions. Issue 18 (12th April 2021) - Duan, Shengzu; Deng, Guogang; Zi, Yujin; Wu, Xiaomei; Tian, Xun; Liu, Zhengfen; Li, Minyan; Zhang, Hongbin; Yang, Xiaodong; Walsh, Patrick J.
Abstract : A unique enantioselective Ni-catalyzed vinylation of 2-azaallyl anions is advanced. This method affords vinyl aryl methyl amine or 1, 3-diamine derivatives with high enantioselectivities, which are frequently occurring scaffolds in medications. Abstract : A unique enantioselective nickel-catalyzed vinylation of 2-azaallyl anions is advanced for the first time. This method affords diverse vinyl aryl methyl amines with high enantioselectivities, which are frequently occurring scaffolds in natural products and medications. This C–H functionalization method can also be extended to the synthesis of enantioenriched 1, 3-diamine derivatives by employing suitably elaborated vinyl bromides. Key to the success of this process is the identification of a Ni/chiraphos catalyst system and a less reducing 2-azaallyl anion, all of which favor an anionic vinylation route over a background radical reaction. A telescoped gram scale synthesis and a product derivatization study confirmed the scalability and synthetic potential of this method.